2017
DOI: 10.17509/ije.v10i1.5085
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Styles of Millennial Generation in University: A Study in Indonesian Context

Abstract: The paper reports a study of the learning styles of Millennial Generation. It aims to identify their learning styles, determine the correlations between their learning styles and their achievements in language skill courses and in a content course, and determine the relationship between the amount of their verbal report of learning styles and their achievement in the content course. A group of 22 learners described how they manage their learning of a content subject. Their written answers were coded to find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
8
0
4
Order By: Relevance
“…Attitude is a picture of each type of human reaction, namely in the main components of emotions, cognitive, and behavior of a person towards something. So, a reflection of the tendency of students' interest in interpreting science can be seen from their attitude towards the lesson itself (Veloo, 2015;Djiwandono, 2017;Manasia, 2015). Attitudes to science are used to show everything a person feels and thinks about science (Sethi, 2015 A scientific attitude is also needed to solve problems.…”
Section: Discussionmentioning
confidence: 99%
“…Attitude is a picture of each type of human reaction, namely in the main components of emotions, cognitive, and behavior of a person towards something. So, a reflection of the tendency of students' interest in interpreting science can be seen from their attitude towards the lesson itself (Veloo, 2015;Djiwandono, 2017;Manasia, 2015). Attitudes to science are used to show everything a person feels and thinks about science (Sethi, 2015 A scientific attitude is also needed to solve problems.…”
Section: Discussionmentioning
confidence: 99%
“…Belum terbiasanya memakai pembelajaran dengan mekanisme blended learning dan daring secara penuh, merupakan rintangan yang besar pada penerapan model pembelajaran jarak jauh. Karena pada umumnya gaya belajar dari generasi ke generasi terdapat perbedaan sesuai dengan perubahan lingkungan dan teknologi yang canggih [5]. Oleh karena itu proses adaptasi dengan perkembangan zaman sudah menjadi kewajiban.…”
Section: Pendahuluanunclassified
“…Students who are not happy with science lessons will tend to be passive and feel lazy during the learning process. [14] More importantly, they suggested that conscious learning is associated with a favorable attitude toward the lesson. However, it turns out that other factors that cause students feel happy or unhappy in science studies depend on the teacher.…”
Section: ) Social Implications Of Natural Sciences 4) Scientist Normmentioning
confidence: 99%